Unsur Perubatan Islam Tibb Nabawi dalam Kitab Bustan Al Salatin dalam Bab Tujuh - SHAMSUDDIN SHUKOR, MASDINIZAM; Wan Ali Wan Mamat (Advances in Humanities and Contemporary Studies, 2025)
This study analyzes the elements of Islamic medicine based on Prophetic Medicine (Tibb Nabawi) in the Bustan al-Salatin book by Nuruddin al-Raniri, focusing on Chapter Seven. Prophetic Medicine according to medical practices based on revelation from the Quran dan the Sunnah of Prophet Muhammad (peace be upon him), which forms the foundation of various traditional health practices in Islamic civilization. Chapter Seven of this work integrates both physical dan spiritual dimensions dalammedical practice, emphasizing the use of Sunnah ingredients such as honey dan black seed (habbatus sauda’) as well as Prophetic guidance in physical and spiritual healing. This research employs a qualitative approach by analyzing the elements of Prophetic Medicine contained in Chapter Seven of Bustan al-Salatin. The findings indicate that the recorded elements of Prophetic Medicine offer holistic health guidance, demonstrating their relevance in the modern context.